صياغة محسنة لمسألة التصميم الأمثل لمقطع I نظامي في جائز رقيق الجدران وملفوف على البارد تناظرياً - محمود سعيد; بادية حيدر (Tishreen University, 2019)
In this paper we one of the structural optimization problems is discussed. It concerns the case of a thin walled beam made by a cold forming procedure. Hereafter, the paper presents an improved formulation of the geometric and technological constraints used in the optimum design problem of a mono-symmetrical I section under a pure bending loading. After formulating this problem properly, the paper proposes an efficient genetic algorithm; then, it shows how to implement it using a MATLAB program. At the end, the effectiveness of this adapted genetic algorithm program is examined by comparing its results with the solution given by the graphical method in a special case. نناقش في هذه المقالة في إحدى مسائل الأمثلة الإنشائية. تعنى هذه المسألة بجائز مقطعه رقيق الجدران. وفيما يلي نقدم صياغة محسنة لقيود التصميم الهندسية (الجيومترية) والتقنية المستخدمة في تصميم مقطع I نظامي وملفوف تناظرياً من صفائح رقيقة تحت تأثير حالة تحميل بعزمين طرفيين. بعد عرض هذه الصياغة، سنقدم خوارزمية جينية ونبين برمجتها باستخدام بيئة ماتلاب. وفي النهاية سنتفحص فعالية هذه الخوارزمية بمقارنة نتائجها مع نتائج الحل التخطيطي الممكن في حالة خاصة.